803 Triple checkpoint blockade, but not anti-PD1 alone, enhances the efficacy of engineered adoptive T cell therapy in advanced ovarian cancer - Anderson, Kristin G; Su, Yapeng; Burnett, Madison G; Bates, Breanna M; Suarez Gutierrez, Magdalia L; Ruskin, Susan L; Voillet, Valentin; Gottardo, Raphael; Greenberg, Philip D (Journal for immunotherapy of cancer, 2023)
BackgroundOver 20,000 women are diagnosed with ovarian cancer annually, and more than half will die within 5 years. This rate has changed little in the last 30 years, highlighting the need for therapy innovation. T cells engineered to express a T cell receptor (TCR) targeting proteins uniquely overexpressed in tumors have the potential to control tumor growth without toxicity. Mesothelin (Msln) contributes to the malignant and invasive phenotype in ovarian cancer and has limited expression in healthy cells, making it a candidate immunotherapy target in these tumors.MethodsThe ID8VEGF mouse cell line was used to evaluate if T cells engineered to express a mouse Msln-specific high-affinity T cell receptor (TCRMsln) can kill murine ovarian cancer. Tumor-bearing mice were treated with TCRMsln T cells plus anti-PD-1, anti-Tim-3 or anti-Lag-3 checkpoint-blocking antibodies alone or in combination, targeting up to three inhibitory receptors simultaneously. Single-cell RNA-sequencing was used to profile the impact of combination checkpoint blockade on the engineered T cells and the tumor microenvironment.ResultsIn a disseminated ID8 tumor model, adoptively transferred TCRMsln T cells preferentially accumulated within established tumors, delayed ovarian tumor growth, and prolonged mouse survival. However, elements in the tumor microenvironment limited engineered T cell persistence and cytolytic function. Triple checkpoint blockade, but not single- or double-agent treatment, dramatically increased antitumor function by intratumoral TCRMsln T cells. Single-cell RNA-sequencing of tumor-infiltrating cells revealed distinct transcriptome changes in engineered and endogenous T cells and myeloid-derived cells. Engineered TCRMsln T cells, when combined with triple checkpoint blockade, increased expression of genes within pathways associated with effector and memory gene signatures, including elevated proliferation and altered metabolic state, and reduced expression of genes associated with exhaustion. Moreover, combining adoptive immunotherapy with triple checkpoint blockade significantly prolonged survival in the cohort of treated tumor-bearing mice, relative to mice that received TCRMsln T cells alone or with anti-PD1 or double-agent treatments.ConclusionsInhibitory receptor/ligand interactions within the tumor microenvironment can dramatically reduce T cell function, suggesting tumor cells may upregulate the ligands for PD-1, Tim-3 and Lag-3 for protection from tumor-infiltrating lymphocytes. In an advanced ovarian cancer model, triple checkpoint blockade significantly improved engineered T cell function and improved outcomes in mice in a setting in which single checkpoint blockade had no significant activity. These results suggest that disrupting multiple inhibitory pathways simultaneously, which can be more safely pursed in a cell intrinsic form through genetic engineering, may be necessary for improved efficacy in patients.Ethics ApprovalThe Institutional Animal Care and Use Committees of the University of Washington and the Fred Hutchinson Cancer Research Center approved all animal studies.